Odpowiedzi

2010-02-22T19:36:28+01:00
1 .
2(x+3)=10
2x+6=10
2x=10-6
2x = 4
x=2

2.

3(1-x)+2=7
3-x+2=-7
-x=-7-3-2
-x=-12
x=12

3.
3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8-1-9
0=0

4.
4(x-2)-2(x-4)=5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0=5


5.
(2y+4)/4=½y+1 /*4
2y+4=2y+4
0=0
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-22T19:38:13+01:00
A)2(x+3)=10
2x+6=10
2x=10-6
2x=4/:2
x=2

b)3(1-x)+2=-7
3-3x+2=-7
-3x=-7-3-2
-3x=-12/:(-3)
x=4

c)3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0



d)4(x-2)-2(x-4)=5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0=5




2.
a)⅗y+⅖=4
3/5y=4-2/5
3/5y=3 i 3/5/: 3/5
y=6



b)(2y+4)/4=½y+1
1/2y+1=1/2y+1
1/2y-1/2y=1-1
0=0



mam nadzieje ze pomogłam. licxe na naj;)
1 1 1